Speech and language development of intercountry adopted children aged 3 to 6 years: An explorative study of Australian parents’ knowledge, beliefs and experiences - Golding, Shannon; Leitão, Suze; Williams, Cori (Routledge, 2013)
This qualitative, explorative study provides an insight into intercountry-adoptive parents’ knowledge, beliefs, and experiences about their children's speech and language development. Eleven parents who lived in Australia and adopted a child aged 3 to 6 years from an overseas country in the past five years completed an online questionnaire. Six consented to participate further in a semistructured interview. Descriptive statistics and thematic analysis were used to report on the parents’ experiences with their adopted children, the challenges they faced, the services they accessed, and their recommendations for future services. The results provide a direction for the development of evidence based service and support to meet the specific needs of this population.